2010
DOI: 10.1063/1.3407439
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of acrolein hydrogenation on Au20 nanoparticle

Abstract: Gold nanoparticles play a key role in catalytic processes. We investigated the kinetics of stepwise hydrogenation of acrolein on Au20 cluster model and compared with that on Au(110) surface. The rate-limiting step barrier of CC reduction is about 0.5 eV higher than that of CO hydrogenation on Au(110) surface. On Au20 nanoparticle, however, the energy barrier of the rate-determining step for CC hydrogenation turns out to be slightly lower than the value for the CO reduction. The selectivity difference on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…According to our recent work on Au(110) [9] and Au 20 [11], radicals bind to substrates via atoms with an unpaired electron favorably.…”
Section: The 5h Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…According to our recent work on Au(110) [9] and Au 20 [11], radicals bind to substrates via atoms with an unpaired electron favorably.…”
Section: The 5h Systemmentioning
confidence: 95%
“…Recently Claus et al [4][5][6]. found that the conventionally catalytically inert gold exhibits unexpected activity for the selective hydrogenation of a, b-unsaturated aldehydes to allyl alcohols, which re-initiates interests on hydrogenation of a, b-unsaturated aldehydes [6][7][8][9][10][11][12]. Acrolein (CH 2 =CH-CH=O) is the first member of a, b-unsaturated aldehyde and its selective hydrogenation to allyl alcohol is most difficult because there are no substitution groups on the carbon atoms of the C=C bond.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[25] For CH 2 @CHACH@O adsorption on small gold clusters, CH 2 @CHACH@O preferentially interacts with the gold cluster via the C@C group rather than the C@O group. [26,27] For both H 2 S and SO 2 adsorption on small gold clusters (which are planar), the sulfur atom is in the same plane and these molecules preferentially adsorb at a single low-coordination gold atom on the gold cluster. [28][29][30][31][32][33] Although impressive progress has been achieved in understanding the adsorption of small molecules on small gold clusters, computational studies for large gold clusters are generally lacking.…”
Section: Previous Calculations For Adsorption Of Small Molecules On Gmentioning
confidence: 99%
“…Although there are many studies in the literature about adsorption of isolated C=C and C=O groups on gold clusters, studies of AC where the C=C and C=O groups are conjugated on gold clusters are relatively fewer [28]. As the adsorption configuration plays a key role in determining hydrogenation selectivity for a, b-unsaturated aldehydes, herein we systematically studied adsorption of AC on the Au n (n = 1-5) clusters.…”
Section: Introductionmentioning
confidence: 98%